KAJIAN LITERATUR TENTANG HABITUS DAN MODAL BUDAYA SISWA DALAM PERSPEKTIF TEORI PIERRE BOURDIEU PADA KONTEKS PENDIDIKAN - Amilatul Fadilah; Muhammad Hanif (PT. Hasba Edukasi Mandiri, 2026)
This study examines the concepts of habitus and cultural capital of students in Pierre Bourdieu’s perspective within the educational context. The background of this research is based on educational inequality that is not only influenced by academic factors but also by social structures shaping students’ dispositions and the distribution of cultural capital within families and schools. The aim of this study is to analyze how habitus and cultural capital are explained in Bourdieu’s perspective, how both operate in educational practices, and to identify research gaps and contributions from previous studies. The method used is a literature review with a systematic literature review approach of relevant journals and books published between 2016–2026. The findings indicate that habitus is formed through long-term internalization of social experiences, while cultural capital serves as a cultural resource influencing students’ achievement, aspirations, and positions within the education system. Education is understood as a field that both reproduces and transforms social structures through the distribution of cultural capital. The conclusion of this study emphasizes that educational inequality is the result of interactions among habitus, cultural capital, and school structure. The recommendation suggests further empirical studies exploring students’ habitus in more specific local contexts and considering contemporary social factors such as digital capital.